Sustainable production of arecanut husk ash as potential silica replacement for synthesis of silicate-based glass-ceramics materials - Anuar, Muhammad Fahmi; Yap, Wing Fen; Azizan, Muhammad Zakwan; Rahmat, Fida’i; Mohd Zaid, Mohd Hafiz; Mohamed Khaidir, Rahayu Emilia; Sheh Omar, Nur Alia (MDPI AG, 2021)
Arecanut husk (AH) was selected as a material for silica replacement in the synthesis process of glass-ceramics zinc silicate and also the fact that it has no traditional use and often being dumped and results in environmental issues. The process of pyrolysis was carried out at temperature 700 °C and above based on thermogravimetric analysis to produce arecanut husk ash (AHA). The average purity of the silica content in AHA ranged from 29.17% to 45.43%. Furthermore, zinc oxide was introduced to AHA and zinc silicate started to form at sintering temperature 700 °C and showed increased diffraction intensity upon higher sintering temperature of 600 °C to 1000 °C based on X-ray diffraction (XRD) analysis. The grain sizes of the zinc silicate increased from 1011 nm to 3518 nm based on the morphological studies carried out by field emission scanning electron microscopy (FESEM). In addition, the optical band gap of the sample was measured to be in the range from 2.410 eV to 2.697 eV after sintering temperature. From the data, it is believed that a cleaner production of low-cost zinc silicate can be achieved by using arecanut husk and have the potential to be used as phosphors materials.